2021
DOI: 10.3389/fcell.2021.621045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124-3p Plays a Crucial Role in Cleft Palate Induced by Retinoic Acid

Abstract: Cleft lip with/without cleft palate (CL/P) is one of the most common congenital birth defects, showing the complexity of both genetic and environmental contributions [e.g., maternal exposure to alcohol, cigarette, and retinoic acid (RA)] in humans. Recent studies suggest that epigenetic factors, including microRNAs (miRs), are altered by various environmental factors. In this study, to investigate whether and how miRs are involved in cleft palate (CP) induced by excessive intake of all-trans RA (atRA), we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 87 publications
0
13
2
Order By: Relevance
“…MEPM cell migration and proliferation play significant roles in the formation of facial structures (He et al, 2008). Many studies have investigated whether atRA inhibits MEPM cell proliferation (Liu et al, 2016;Liu et al, 2021;Yoshioka et al, 2021;. However, the molecular mechanism by which HSL affects cell migration and proliferation needs to be fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…MEPM cell migration and proliferation play significant roles in the formation of facial structures (He et al, 2008). Many studies have investigated whether atRA inhibits MEPM cell proliferation (Liu et al, 2016;Liu et al, 2021;Yoshioka et al, 2021;. However, the molecular mechanism by which HSL affects cell migration and proliferation needs to be fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive atRA, DEX, and phenytoin induce CP in mice [24,39,40]. Excessive atRA induces CP through upregulated miR-124-3p expression [11], and DEX induces miR-130b and miR-155 in porcine pre-adipocytes and differentiating 3T3-L1 pre-adipocytes, respectively [41,42]. DEX also inhibits miR-132 expression through TGF-β signaling in pancreatic cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that overexpression of miR-374a, miR-133b, and miR-4680-3p inhibits cell proliferation in cultured human palatal mesenchymal cells [9]. In addition, exposure to all-trans retinoic acid (atRA) alters the expression of miR-106-5p [10] and miR-124-3p [11] in mouse embryonic palatal shelves. A growing amount of evidence shows that miRNAs play crucial roles in development and pathological conditions; therefore, it is important to identify how the expression of miRNAs is altered under specific conditions and in presence of chemicals known to cause of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to several chemicals (e.g., retinoic acid, dexamethasone, dioxins) induces cleft palate in mice and in humans [ 124 , 125 , 126 ]. Retinoic acid ( at RA) induces expression of miR-124-3p [ 127 , 128 ] and miR-106-5p [ 129 ] in cultured MEPM cells and the developing palatal shelves in mice. miR-124-3p can inhibit cell proliferation through suppression of genes crucial for palate development, and miR-106-5p induces apoptosis and compromises phosphatidylcholine synthesis/cell membrane synthesis though suppression of Tgfbr2 .…”
Section: Micrornas Involved In Chemical-induced Cleft Lip and Cleft P...mentioning
confidence: 99%